Synthesis, characterization and host-guest complexes of supramolecular assemblies based on calixarenes and cucurbiturils - Baa, Ebenezer (Rhodes University, Faculty of Science, Department of Chemistry)
The field of supramolecular chemistry has grown large and wide in both deepness of understanding, range of topics covered and scope and applications. Supramolecular self-assemblies are facilitated by a wide range of non-covalent intra and inter molecular interactions that range from hydrogen bonding to Ï€-interaction and van der Waals. Macrocyclic compounds such as cucurbiturils and calixarenes have emerged as important classes of compounds with excellent potential of forming supramolecular assemblies. The porous nature of these compounds enables them to form host-guest supramolecular complexes stabilized by diverse range of non-covalent interactions. Furthermore, these compounds contain donor atoms capable of forming bonds with metal ions to yield metal complexes with interesting porous characteristics that deviate from their traditional hydrophobic cavity. The versatile nature of the resulting pores imply that they can accommodate diverse types of guests. This work explores the synthesis and characterization of a host of calixarenes and cucurbiturils. Self-assembly of these macrocycles with various metal ions results to the formation of porous metal organic framework (MOF) complexes. Four new calixarene typed compounds obtained from aromatic aldehydes and twenty-six cucurbituril metal complexes are reported. These macrocylces and their metal complexes also form supramolecular complexes with DMSO, methanol, isoniazid hydrochloride and ciprofloxacin hydrochlorides through either self-assembly, mechanochemistry and exposure to solvent vapors. The bulk materials have been characterized using nuclear magnetic resonance spectroscopy (NMR), Fourier transformed infrared spectroscopy (FTIR), powder and single crystal diffraction techniques and thermal studies thermogravimetric analysis (TGA) and differential thermal calorimetry (DSC). Data obtained from this study reveals that calixarenes can form supramolecular complexes with a frequently used laboratory solvents with BN22 showing appreciable selectivity for DMSO sorption from a solvent mixture. These compounds also form supramolecular complexes with drug molecules such as isoniazid and ciprofloxacin. Furthermore, the data reveals that choice of synthetic route of supramolecular ensembles dictates if the guest drug molecule will occupy the intrinsic or extrinsic pores of cucurbituril complexes. Biological studies on the obtained complexes reveal that the cucurbituril complexes are non-cytotoxic while the calixarenes show antibacterial activity against Escherichia coli and Staphylococcus aureus. Additionally, the study showed that ciprofloxacin can be successfully released from a calixarene host in a simulated body fluid although the host was also found to cross the dialysis membrane. The results of this study are important in that; - they can be exploited and developed in the selective sorption of certain guests and - that they can be used in the development of drug delivery systems that play a dual role of delivery and therapeutic activity.
Keywords: Supramolecular chemistry; Calixarenes; Cucurbiturils; Metal-organic frameworks; Macrocyclic compounds; Drug delivery systems